The Role of Political Parties in Realizing Democracy in the 2024 Elections in Indonesia - Budiawan, Asep; Pudjiastuti, Diah; Santoso, Bagus (PINISI Discretion Review, 2025)
The 2024 General Election in Indonesia serves as a critical momentum to assess the extent to which political parties contribute to the realization of substantive democracy. In the political reality, political parties as the main pillars of democracy function not only as institutions for political recruitment but also as agents of political education, interest aggregation, and the strengthening of public representation. However, electoral practices are often marked by pragmatism, money politics, and internal party oligarchy, which create a gap between the ideal expectations of democracy and the realities on the ground. This study aims to analyze the role of political parties in realizing democracy during the 2024 elections by examining how parties perform their democratic functions and the extent of their influence on the quality of democracy. The research employs a qualitative method with a descriptive-analytical approach, utilizing literature review, secondary data analysis, and a critical examination of political regulations and practices in Indonesia. The findings reveal that political parties still face serious challenges in achieving an ideal democratic system, particularly due to weak cadre development, elite domination, and the lack of transparency in party governance. Nevertheless, there are opportunities for political parties to strengthen democracy through internal party reform, the enhancement of public political education, and consistent adherence to the principles of justice and political participation. The study concludes that the role of political parties in the 2024 elections is crucial in determining the direction of democratic consolidation in Indonesia. Therefore, it is recommended that political parties strengthen their cadre systems, improve accountability, and avoid transactional political practices in order to promote a healthier and more equitable democracy.